Solve the system:  6x + 3y = 12 8x + 9y = 26. 

Solve the first equation (6x + 3y = 12) for y: Click here to see how. (In general, you just need to solve one of the equations for one of the variables.) 
y = 2x + 4  
Substitute this expression for y into the second equation:  8x + 9(2x + 4) = 26.  
Simplify:  10x + 36 = 26.  
Solve for x: Click here to see how. 
x= 1.  
Substitute this value for x into one of the original equations:  6(1) + 3y = 12.  
Solve for y:  y = 2.  
Final Answer:  x = 1, y = 2. 


